2012
DOI: 10.1016/j.exer.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Iodoacetic acid, but not sodium iodate, creates an inducible swine model of photoreceptor damage

Abstract: Our purpose was to find a method to create a large animal model of inducible photoreceptor damage. To this end, we tested in domestic swine the efficacy of two chemical toxins, known to create photoreceptor damage in other species: Iodoacetic Acid (IAA) and Sodium Iodate (NaIO3). Intravenous (IV) administration of NaIO3 up to 90 mg/kg had no effect on retinal function and 110 mg/kg was lethal. IV administration of IAA (5 – 20 mg/kg) produced concentration dependent changes in visual function as measured by ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
1
36
2
Order By: Relevance
“…The IAA has been extensively used as an effective tool to selectively eliminate retinal photoreceptors in a variety of species for the last 60 years [1,3,4,10,11,14,22]. As observed in other species, the toxic effects of IAA treatment are dose dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IAA has been extensively used as an effective tool to selectively eliminate retinal photoreceptors in a variety of species for the last 60 years [1,3,4,10,11,14,22]. As observed in other species, the toxic effects of IAA treatment are dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is technically challenging and the dosage of IAA for complete rods and cones removal remains to be determined. It was reported that, after a swine received a single injection of IAA via ear vein (20 mg kg 1 ), at two weeks post-IAA there was no rod-or cone-driven ERG response [11]. Thus, it is plausible that ear vein injection is more effective than limb vessel delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, wild-type pigs are being used as models already. Wild-type pigs are particularly useful for studying cardiovascular disease (2), atherosclerosis (3), cutaneous pharmacology (4), wound repair (5), cancer (6), diabetes (7), and ophthalmology (8). In many cases, they are the species of choice for translational medicine (9, 10).…”
Section: Importance Of Pigs As Biomedical Modelsmentioning
confidence: 99%
“…22 To date, several porcine models of photoreceptor degeneration have been proposed, 23,24 including the transgenic miniature swine, for example, the TgP23H model of retinitis pigmentosa, 24 or induced by an intravenous injection of iodoacetic acid (IAA). 21,25,26 The latter chemical compound causes an inhibition of anaerobic glycolysis through the reaction with the glyceraldehyde-3-phosphate dehydrogenase. 27 Photoreceptors are affected by IAA injection in a dosedependent manner (assessed between 7.5 and 12 mg/kg), with a decrease in production of energy and eventually death.…”
mentioning
confidence: 99%